DOMINANT IDEOLOGY IN PRESIDENT BARACK OBAMA IN HIS OWN WORDS: A CRITICAL DISCOURSE ANALYSIS - YUNIATI, NUR AMINI (2011)
The problem of this study is how the dominant ideology is reflected in President Barack Obama in His Own Words. The objective of this study is to analyze the President Barack Obama in His Own Words based on the critical discourse analysis and to reveal the dominant ideology underlying the book. This study is qualitative study. The data sources used in this study are primary and secondary data sources. The primary data source is the President Barack Obama in His Own Words book. The secondary data sources are both the article on the internet and news paper review which contains Barack Obama's ideology and other sources, which are related to the analysis. The method of data collection is library research and the technique of data collection is descriptive technique. The conclusions of the study are as follows: Firstly, the dominant ideology in the book of President Barack Obama in His Own Words is democracy ideology. Secondly, the ideologies in the book of President Barack Obama in His Own Words are capitalism, globalism, democracy, and liberalism. Thirdly, the book of President Barack Obama in His Own Words represents Obama's media socio-political account of his campaign to access power relations and supports character of Obama's Ideology. It also serves as political representations in Obama's minds to communicate events in the reproduction of dominance and inequality.